Chiral multifunctional thiourea-phosphine catalyzed asymmetric [3 + 2] annulation of Morita–Baylis–Hillman carbonates with maleimides - Deng, Hong-Ping; Wang, De; Wei, Yin; Shi, Min (Beilstein Journal of Organic Chemistry, 2012)
We have developed a multifunctional thiourea-phosphine catalyzed asymmetric [3 + 2] annulation of Morita–Baylis–Hillman (MBH) carbonates with maleimides, which can efficiently construct functionalized cyclopentenes bearing three contiguous stereocenters in moderate to excellent yields and excellent diastereo- and enantioselectivities. A plausible mechanism has been also proposed on the basis of control experiments and previous literature.
Keywords: asymmetric [3 + 2] annulation; maleimides; Morita–Baylis–Hillman carbonates; multifunctional thiourea-phosphine; organocatalysis